Towards a fuzzy logic model for chemical risk assessment by inhalation in laboratories - Obando, Óscar; Garita-Rodríguez, César (Proceedings of the 2015 IEEE 35th Central American and Panama Convention, CONCAPAN 2015, 2015)
This paper presents a computational Fuzzy Logic Model for chemical hazards risk assessment by inhalation in laboratories. Some influence factors on chemical risk are deterministic but not completely measurable. As a result, this research focusses on Fuzzy Logic, instead of a probabilistic approach. Data for simulation is based on a hypothetical but completely realistic laboratory. Dependency on time has been identified as an important factor, describing events on the laboratory installation. Exposure levels for individual factors, labor hours and general health overcome current known strategies used on risk assessment. These conditions are included in the proposed model.
Conferencia
Keywords: Riesgos; Modelado; Factores humanos; Factores de riesgos; Laboratorios; Research Subject Categories::TECHNOLOGY::Chemical engineering::Chemical process and manufacturing engineering::Process chemistry; Research Subject Categories::TECHNOLOGY::Information technology::Computer science